Factor VII-401 and -402 polymorphisms and acute myocardial infarction in southern Turkey population - Dönmez, Yurdaer; Koca, Hasan; İçen, Yahya Kemal and Demirtaş, Mustafa (The European Research Journal, 2019)
Objectives: Factor VII has a crucial role in the extrinsic coagulation pathway and initiates the thrombus formation. Some studies showed that high plasma factor VII level was related to increased acute myocardial infarction (AMI) risk. But, some studies were reported opposite findings. Some polymorphisms can change the factor VII level. There is limited information about factor VII polymorphisms in southern Turkey population. Our aim was to determine the frequencies of Factor VII-401 and -402 polymorphisms and their relation to AMI in southern Turkey area. Methods: We enrolled 83 patients with AMI and 71 healthy subjects. Routine laboratory tests and factor VII-401 and -402 polymorphisms were determined from blood samples. Factor VII -401 and -402 polymorphisms were analyzed by LightCycler device using Real-Time PCR technique. Results: Family history of coronary artery disease and smoking frequencies were higher in patients group (p < 0.001 and p = 0.013, respectively). Patients had higher LDL cholesterol (p = 0.011) level, and lower HDL cholesterol (p = 0.025) level compared to healthy subjects. Factor VII-401 and -402 polymorphism genotypes were not significantly different in both groups. Also allele frequencies were similar in both groups. Conclusion: Factor VII-401 and -402 polymorphisms do not seem to increase AMI risk in southern Turkey.